Clinical and virological features of acute HBV-related hepatitis in southern Vietnam - Yen-Xuan Thi Nguyen; Dieu-Hien Tran Pham; Nga Ngoc Cao; Lory Saveria Crocè (Annals of Hepatology, 2006)
Background: Despite the availability of effective vaccines, hepatitis B virus (HBV) infection is still frequent worldwide, and accounts for significant morbidity and mortality. However, data of acute HBeAg negative hepatitis still remain limited. Aims and Methods: To understand clinical pictures of acute HBV hepatitis and its natural evolution, a prospective study was conducted in adult patients. Results: Ninety patients were enrolled between March 2004 and April 2005 at Hospital for Tropical Diseases in Ho Chi Minh city. The prevalence of HBeAg negative was 53%. No significant difference was found in clinical characteristics and laboratory findings between HBeAg positive and negative patients. HBV-DNA was detected in 75% and 88% HBe negative and positive patients, respectively, where the frequency of ALT below 400 U/L was significantly higher in HBeAg negative cases (p = 0.01). Six month follow-up was available in 47 patients. HBsAg positivity was found in 16% of HBeAg negative subjects but only in 4.5% of HBeAg positive cases. Thirty two patients had neither HBsAg nor anti-HBs. Conclusions: The clinical and laboratory feature and the outcome at 6 months of HBV acute hepatitis in Vietnam is similar in HBeAg positive and negative patients.